O10 Should sexual health services participate in the HPV vaccination programme? A national survey assessing HPV vaccination uptake in young GUM attendees. (23rd May 2012) - Sacks, R; Robinson, A; Wilkinson, D
Abstract : Background: In 2008, a schools-based HPV vaccination programme was introduced for girls aged 12–13, with an accelerated catch up programme for those aged 14–18. A significant impact on cervical cancer rates requires 80% uptake of three vaccinations, however in England the completion rate was 58% in 2009/10. Aim: To compare HPV vaccination outcomes and prevalence of risk factors, associated with HPV acquisition and cervical cancer development, in young women attending GUM clinics with national data. Method: An anonymous questionnaire was given to 13–19 y/old women attending 19 participating GUM clinics from March to August 2011. Data were analysed using multivariate linear regression in SPSS. Results: 2247 questionnaires were completed (median respondent age 17). Compared to national data, respondents were more likely to be smokers (48% vs 12% of 15 y/olds), have had coitarche aged <16 (52% vs 26%), have had an STI previously (29% vs 13% for <16 coitarche) or not be in education, employment or training (NEET) (8% vs 2% of 16 y/olds). Of the 74% offered the vaccination, 81% accepted. Of those accepting the vaccination, 81% had all three injections. Of those who had <3 doses, 65% reported no active recall. Overall, 47% of all respondents had received all three vaccine doses. Completion rates were lower in London, non-white ethnicities, 17–19 y/olds, NEETs, smokers and those with previous Chlamydia (all p<0.0001). Discussion: The study population exhibited lower HPV vaccination completion rates than the national average, demonstrating that GUM attendees are a harder-to-reach group through current PCT delivery programmes. This population also exhibited higher rates of risk factors for HPV acquisition, highlighting GUM attendees as a priority target group for HPV vaccination. This data demonstrates the potential role of GUM clinics as supplementary HPV vaccination delivery sites, in targeting at-risk young women with low uptake of the HPV vaccination.